Vapor-Liquid Equilibrium of Carbon Dioxide plus Ethyl Acetate plus Oleic Acid Mixtures at High Pressures - Ferreira-Pinto, Leandro; Zanette, Andreia [UNESP]; Pedersen Voll, Fernando Augusto; Cabral, Vladimir Ferreira; Castier, Marcelo; Cardozo-Filho, Lucio (Amer Chemical Soc, 2017)
In this work, experimental data for the phase transition of ternary systems {CO2 (1) + ethyl acetate (2) + oleic acid (3)} at global CO2 mole fraction values from 0.5 to 1, at the temperatures of 308, 318, 328, and 338 K are reported. A variable volume cell was used, following the static synthetic method for pressures of up to 21 MPa. The ethyl acetate/oleic acid molar ratio was set to 3:1 [0.750 ethyl acetate + 0.250 oleic acid], 9:1 [0.900 ethyl acetate + 0.100 oleic acid], and 199:1 [0:995 ethyl acetate + 0.005 oleic acid]. In all of these ternary systems, bubble point and dew points were observed.